2016
DOI: 10.1210/en.2015-2052
|View full text |Cite
|
Sign up to set email alerts
|

ATR-101, a Selective and Potent Inhibitor of Acyl-CoA Acyltransferase 1, Induces Apoptosis in H295R Adrenocortical Cells and in the Adrenal Cortex of Dogs

Abstract: ATR-101 is a novel, oral drug candidate currently in development for the treatment of adrenocortical cancer. ATR-101 is a selective and potent inhibitor of acyl-coenzyme A:cholesterol O-acyltransferase 1 (ACAT1), an enzyme located in the endoplasmic reticulum (ER) membrane that catalyzes esterification of intracellular free cholesterol (FC). We aimed to identify mechanisms by which ATR-101 induces adrenocortical cell death. In H295R human adrenocortical carcinoma cells, ATR-101 decreases the formation of chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 54 publications
3
61
1
Order By: Relevance
“…ATR-101 administration reduces the levels of circulating steroids in mice with ACC cell xenografts and in dogs stimulated with ACTH (Cheng et al, 2016;Lapensee et al, 2016). Some MDR1 inhibitors reduced circulating corticosteroid levels in clinical trials, suggesting that MDR1 inhibition can reduce steroid secretion in man (Guthrie et al, 1983;Shapiro et al, 1990;Kobayashi et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ATR-101 administration reduces the levels of circulating steroids in mice with ACC cell xenografts and in dogs stimulated with ACTH (Cheng et al, 2016;Lapensee et al, 2016). Some MDR1 inhibitors reduced circulating corticosteroid levels in clinical trials, suggesting that MDR1 inhibition can reduce steroid secretion in man (Guthrie et al, 1983;Shapiro et al, 1990;Kobayashi et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Acyl-coenzyme A: cholesterol acyltransferase (ACAT) inhibition was proposed to cause cholesterol accumulation and cytotoxicity in ACC cell lines (Sbiera et al, 2015;Lapensee et al, 2016). Most ACAT inhibitors do not cause cholesterol accumulation or cytotoxicity under normal cell culture conditions, and differences in the ACAT inhibitory activities of different compounds do not correlate with differences in cytotoxicity (Junquero et al, 2001;Rodriguez and Usher, 2002;An et al, 2008;Pokhrel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of dogs with ATR-101 decreased the formation of corticosteroids and induced adrenocorticocytes apoptosis, followed by a decrease in the adrenal cortex. The authors suggested that the use of ATR-101 (the ACAT inhibitor) may be promising in the treatment of adrenalcortical cancer [47]. In H295 cells, o,p'-DDD dramatically increased the expression of reticular stress marker CHOP (transcription factor encoded by the ddIT3 gene) [44].…”
Section: The Scheme Of Mitochondrial Processes Affected By Op'-dichlmentioning
confidence: 99%
“…ATR-101 treatment of H295R cells led to the accumulation of free fatty acids and cholesterol that induces ER stress [47]. In so doing the increased caspase 3/7 activity and activation of apoptosis, assessed by terminal deoxynucleotidyl transferase nick end labe-…”
mentioning
confidence: 99%